2017
DOI: 10.1002/anie.201704613
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Carbon Dioxide Electroreduction to Carbon Monoxide over Defect‐Rich Plasma‐Activated Silver Catalysts

Abstract: Efficient, stable catalysts with high selectivity for a single product are essential if electroreduction of CO is to become a viable route to the synthesis of industrial feedstocks and fuels. A plasma oxidation pre-treatment of silver foil enhances the number of low-coordinated catalytically active sites, which dramatically lowers the overpotential and increases the activity of CO electroreduction to CO. At -0.6 V versus RHE more than 90 % Faradaic efficiency towards CO was achieved on a pre-oxidized silver fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
164
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(175 citation statements)
references
References 32 publications
(3 reference statements)
8
164
0
3
Order By: Relevance
“…Cu NPs/ZnO and Ag NPs/ZnO were also investigated for comparison . As shown in Figure a, the Ag 3d binding energies of these three Cu−Ag NPs/ZnO are approximately 367.9 eV and 373.7 eV (corresponding to Ag 0 ), while those of Ag NPs/ZnO are 367.3 eV and 373.3 eV (corresponding to Ag + ),, suggesting that the Ag species in these three Cu−Ag NPs/ZnO had an enhanced antioxidant capacity compared with Ag NPs/ZnO. More interesting, we found the similar results in the Cu 2p signals (Figure b).…”
Section: Figuresupporting
confidence: 66%
“…Cu NPs/ZnO and Ag NPs/ZnO were also investigated for comparison . As shown in Figure a, the Ag 3d binding energies of these three Cu−Ag NPs/ZnO are approximately 367.9 eV and 373.7 eV (corresponding to Ag 0 ), while those of Ag NPs/ZnO are 367.3 eV and 373.3 eV (corresponding to Ag + ),, suggesting that the Ag species in these three Cu−Ag NPs/ZnO had an enhanced antioxidant capacity compared with Ag NPs/ZnO. More interesting, we found the similar results in the Cu 2p signals (Figure b).…”
Section: Figuresupporting
confidence: 66%
“…It was also reported that structure, morphology, size, and composition of the catalyst can lead to adsorption and decoupling site preferences of different adsorbates of C bound on the surface and further result in the breaking of the linear scaling relationships and tuning of the adsorption strength, eventually exerting a dramatic influence on the ECR performance . Indeed, in addition to polycrystalline and single‐crystalline Ag, some new A types have been developed and characterized recently, such as nanostructured Ag with different sizes, supported Ag catalysts with different substrates including C, TiO 2 , Al 2 O 3 , dopant‐aided Ag, oxide‐derived Ag, and surface‐modified Ag …”
Section: Advances In Ag‐based Co2‐to‐co Electrocatalystsmentioning
confidence: 99%
“…To get in‐depth understanding how the subsurface O and cationic metal species can tune the structure and morphology of Ag catalysts as well as further optimize reaction kinetics and pathways in the ECR to CO, Mistry et al. synthesized OD‐Ag catalysts by the treatment of Ag foils in low‐pressure plasma of O 2 gas . Compared to the counterpart metallic Ag foil, the OD‐Ag catalyst with O 2 plasma treatment displayed an FE of CO of more than 90 % at a low potential of −0.6 V versus RHE in 0.1 m KHCO 3 .…”
Section: Advances In Ag‐based Co2‐to‐co Electrocatalystsmentioning
confidence: 99%
“…The presence of oxygen in the deep bulk of o‐Ag 2 O‐5h can be related to the large size of o‐Ag 2 O that makes the electrochemical reduction of the deep bulk kinetically slow. The survival of oxygen in a silver foil pre‐oxidized by oxygen plasma during electrochemical CO 2 reduction was also observed very recently …”
Section: Figurementioning
confidence: 99%